Synthesis of Natural Clay Magnetite Composite as Adsorbent of Methylene Blue - I Made Sadiana; Abdul Hadjranul Fatah; Karelius Karelius (Jurnal Sains dan Terapan Kimia, 2017)
Synthesis of natural clay magnetite composite has been done. The composite was applicated as adsorbent of methylene blue dye in aqueous solution. natural clay was activated with acid solution, synthesis of natural clay magnetite composite was done by coprecipitation method in the molar ratio Fe2+: Fe3+ = 1 : 2 at temperature 85οC. Characterization of the synthesis results is done by XRD and FTIR. Adsorption using batch system with the optimum pH, kinetic and equilibrium aspects of adsorption were studied. The characterization results shows that iron oxide Fe3O4 (magnetite) can be composited with natural clay. The activated and natural clay magnetite composite can adsorbed methylene blue dye from aqueous solution, with the optimum adsorption at pH 3. Adsorption of those adsorbent followed the kinetic eqution of pseudo order 2 with reaction rate constant for activated and natural clay magnetite composite was 1.68 x 10-3 and 7.13 x 10-3 g/mg.minute. The isotherm adsorption is Langmuir isotherm with adsorption capacity was 1.72 x 10-4 mol/g and 1.84 x 10-4 mol/g. This kinetic reactions model shows that the natural clay magnetite composite is able to adsorbed rhodamine B in aqueous solution and accelerated separation of adsorbent from aqueous phase by external magnet field.Keywords: natural clay, magnetite, composite and adsorption.